The Dividend and Earnings Behaviour of Firms on the Kuala Lumpur Stock Exchange - Md Nassir, Annuar; Mohamad, Shamsher (Universiti Putra Malaysia Press, 1993)
The dividend and earnings behaviour of firms in developed economies are well documented. In Malaysia, there is hardly any published evidence on these issues. This study investigates the dividend and earnings behaviour of firms listed on the Kuala Lumpur Stock Exchange (KLSE). The findings suggest that: (i) the dividend decisions of these firms partially depend on their current earnings and past dividends; (ii) firms have long-term target dividend which is conditioned upon their earnings ability, and (iii) earnings changes of firms are random which implies that earnings forecasts by analysts might be of no economic significance.